2016
DOI: 10.1073/pnas.1604153113
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of iPSC-derived TM cells rescues glaucoma phenotypes in vivo

Abstract: Glaucoma is a common cause of vision loss or blindness and reduction of intraocular pressure (IOP) has been proven beneficial in a large fraction of glaucoma patients. The IOP is maintained by the trabecular meshwork (TM) and the elevation of IOP in open-angle glaucoma is associated with dysfunction and loss of the postmitotic cells residing within this tissue. To determine if IOP control can be maintained by replacing lost TM cells, we transplanted TM-like cells derived from induced pluripotent stem cells int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(140 citation statements)
references
References 54 publications
3
137
0
Order By: Relevance
“…A number of ocular surface diseases involve loss of cells on the surface and endothelium of the cornea (Ahmad, 2012). For all of these ocular diseases, researchers have proposed that stem cell-based therapy could be used to restore tissue health and function (Abu-Hassan et al, 2015; Al-Shamekh and Goldberg, 2014; Erbani et al, 2016; Mead et al, 2015; Nakamura et al, 2016; Roubeix et al, 2015; Zhu et al, 2016). One strategy for replacing lost cells is to transplant stem cells into the affected areas where they differentiate into the desired cell type and restore tissue/organ function (Blenkinsop et al, 2012).…”
Section: Stem Cells and Exosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of ocular surface diseases involve loss of cells on the surface and endothelium of the cornea (Ahmad, 2012). For all of these ocular diseases, researchers have proposed that stem cell-based therapy could be used to restore tissue health and function (Abu-Hassan et al, 2015; Al-Shamekh and Goldberg, 2014; Erbani et al, 2016; Mead et al, 2015; Nakamura et al, 2016; Roubeix et al, 2015; Zhu et al, 2016). One strategy for replacing lost cells is to transplant stem cells into the affected areas where they differentiate into the desired cell type and restore tissue/organ function (Blenkinsop et al, 2012).…”
Section: Stem Cells and Exosomesmentioning
confidence: 99%
“…Embryonic stem cell (ESC) derived precursors and induced pluripotent stem cells (iPSCs) have also been transplanted to replace degenerated photoreceptors and RPE cells (Gonzalez-Cordero et al, 2013; Meyer et al, 2009). In the trabecular meshwork, iPSCs have been used to repopulate the meshwork and/or provide trophic factors that induce proliferation in endogenous cells (Abu-Hassan et al, 2015; Zhu et al, 2016). …”
Section: Stem Cells and Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggested not only low TM cellularity (Alvarado, Murphy & Juster, 1984;Baleriola et al, 2008), but also TM cytoskeleton and phagocytosis changes in primary open angle glaucoma (Clark et al, 1995;Fatma et al, 2009;Izzotti et al, 2010;Saccà, Pulliero & Izzotti, 2015;Peters et al, 2015;Micera et al, 2016). Repopulating diseased TM with fresh, functional TM cells has been shown to restore homeostasis of normal outflow and thus might represent a novel therapeutic breakthrough (Du et al, 2013;Abu-Hassan et al, 2015;Yun et al, 2016;Zhu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In glaucomatous eyes, diseased TM has a reduced facility and shows reduced phagocytosis [25,26], increased stiffness [27], and stress fiber formation [26]. Either removing TM surgically [28] or rehabilitating TM function by stem cells [29] can restore normal outflow and decrease IOP in previous studies. In the current study, our results showed that ab interno trabeculectomy with the Trabectome efficiently reduced IOP and the number of glaucoma medications with an overall success rate of 76% during a 2-year follow-up.…”
Section: Discussionmentioning
confidence: 98%